Improving The Ability Of Subtracting Small Numbers By Large Numbers Using The Jurang Board Media For 2nd Grade Elementary School Students At Sdn 4 Gondang In The 2024/2025 Academic Year - Surhana Surhana; M. Taufik; Maulida Arum Fitriana (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to determine the effectiveness of using a cliff board in improving the ability of second-grade students at SDN 4 Gondang in subtraction operations between small and large numbers. This study is a classroom action research (CAR) conducted in two cycles. Each cycle consists of two sessions, each allocated 2×35 minutes per session. Each cycle includes the stages of planning, implementation, observation, and reflection. Data was collected through post-test assessments at the end of each cycle and observations of teacher and student activities during instruction. The results of the study indicate an improvement in student learning outcomes, with the average student score increasing from 54 in Cycle I to 84.5 in Cycle II. Student learning achievement also improved significantly from 45% in Cycle I to 90% in Cycle II. Thus, the use of the abacus board medium was proven effective in improving students' ability in subtraction operations.